The Uninsured Deposit Premium - Daniel Dias; Tim Schmidt-Eisenlohr (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We estimate the uninsured deposit premium - the difference between the rates paid on uninsured versus insured deposits - by linking observed average deposit rates to an estimated share of uninsured deposits. Using U.S. bank data from 1991 to 2025, we show that the average uninsured deposit premium rose by nearly 400 basis points over this period. This rise reflects both falling insured deposit rates and rising uninsured deposit rates. We find a strong correlation with the monetary policy cycle: a one-percentage-point increase in the Federal Funds Rate corresponds to a rise of roughly 32 basis points in the uninsured deposit premium. We develop a bargaining model between banks, insured depositors, and uninsured depositors that explains these dynamics.
Keywords: E52; G21; G28; 330; uninsured deposits; monetary policy; bank funding; deposit pricing